Good Practice Example and a Success Story from the European Commission - Kosmas, Petros C. (My University, 2026)
Award: Good Practice Example and a Success Story from the European Commission European Project Leonardo da Vinci (LdV)-Transfer of Innovation (TOI) project: “SmartFarmer: Improving skills for SmartFarming as an innovative tool for rural development and economic growth”.
Keywords: Social sciences